Ventilation of buildings - Doane, May (My University, 1904)
Introduction: Ventilation is the changing of the air in a room by withdrawing the impure air and substituting pure air from the outside. Thorough ventilation is necessary. Though the air in a room does not differ from that without, if the room is inhabited by one or more individuals the air in the room even deteriorates until the impurities therein reach a certain degree which is incompatible with health. This is due to the fact that with each breath a certain quantity of carbon dioxide organic impurities and aqueous vapor is exhaled. These products of respiration soon contaminate the air in the room until it is rendered impure and unfit for breathing. Besides the impurities caused by breathing, there are also those which are given off by the skin. The secretion of the skin consists of survat which is an acid watery fluid, containing about 1.8 percent of solids and of sebaceous matter. The quantity varies greatly according to the temperature and humidity of the air but may be takin as ranging from 800 to 1000 cu cm during twenty four hours. Epithelial cells are also being constantly disengaged from the skin and a considerable quantity of carbon dioxide is given off through the skin.
Citation: Doane, May. Ventilation of buildings. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Ventilation; Buildings; Air Quality; Science; Science of Ventilation; Theses; Manuscripts (documents)